2012
DOI: 10.1177/0148607112446703
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile

Abstract: Clostridium difficile is the leading cause of healthcare-associated infectious diarrhea. Although C difficile is part of normal flora in some healthy individuals, patients with selective risk factors are often vulnerable to the toxigenic potential of this virulent healthcare pathogen. The spectrum of C difficile infection (CDI) is highly variable, ranging from mild to severe illness, presenting with single to multiple disease recurrences. Current approaches to treatment are based on severity of illness, number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 143 publications
0
16
0
Order By: Relevance
“…C . difficile infections have primarily been associated with individuals undergoing antibiotic therapy, but long hospitalizations, underlying comorbidities, community-acquired infections, and age-related risk factors have also been documented [ 4 6 ]. These complications lead to C .…”
Section: Introductionmentioning
confidence: 99%
“…C . difficile infections have primarily been associated with individuals undergoing antibiotic therapy, but long hospitalizations, underlying comorbidities, community-acquired infections, and age-related risk factors have also been documented [ 4 6 ]. These complications lead to C .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, diagnostic tests for CDI are stool culturing, cell cytotoxicity neutralization assay, enzyme immunoassay (EIA) for toxins A and B, detection of C. difficile glutamate dehydrogenase (GDH), and polymerase chain reaction (PCR) detection of C. difficile genes [ 10 ]. Culturing diagnosis is very sensitive, but the turnaround time can be up to 3–5 days [ 11 ]. GDH testing is very sensitive but is not specific and requires additional EIA for toxin A and/or toxin B [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Culturing diagnosis is very sensitive, but the turnaround time can be up to 3–5 days [ 11 ]. GDH testing is very sensitive but is not specific and requires additional EIA for toxin A and/or toxin B [ 11 , 12 ]. There are multiple commercial EIA kits for toxin A/B detection on the market, but their sensitivities vary and they may not be available in all countries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased economic burden in hospitalized patients due to CDI has been estimated at $9,822 to $13,854 per patient, and total patient costs (health care costs plus lost wages) associated with CDI have been estimated to exceed $1 billion annually in the United States alone (3,4). Several recent studies have demonstrated that rapid and accurate detection of C. difficile is an important component of combating hospital-acquired CDI and can have a significant benefit to patients and hospitals from a financial and clinical perspective (4)(5)(6).…”
mentioning
confidence: 99%